Mushroom Oils: A Review of their Production, Composition, and Potential Applications - Rui Yeong Tan; Zul Ilham; Wan Abd Al Qadr Imad Wan-Mohtar; Sarina Abdul Halim-Lim; Siti Rokhiyah Ahmad Usuldin; Rahayu Ahmad; Muhammad Adlim (Elsevier Ltd., 2024)
Indexed by WOS/ Scopus